Transport of d-Arabinose-5-Phosphate and d-Sedoheptulose-7-Phosphate by the Hexose Phosphate Transport System of Salmonella typhimurium - Eidels, Leon (1974)
d-Arabinose-5-phosphate and d-sedoheptulose-7-phosphate were found to be substrates, although not inducers, of the hexose phosphate transport system of Salmonella typhimurium. Transport of these two sugar phosphates by wild-type strains required preinduction of the hexose phosphate transport system. A mutant of S. typhimurium constitutive for this system also transported d-arabinose-5-phosphate and d-sedoheptulose-7-phosphate in a constitutive fashion. Glucose-6-phosphate was a potent competitor of the transport of both d-arabinose-5-phosphate and d-sedoheptulose-7-phosphate. The K(m) values for transport of d-glucose-6-phosphate, d-arabinose-5-phosphate, and d-sedoheptulose-7-phosphate were 0.13, 0.32 and 1.61 mM, respectively. The apparent V(max) values for transport of d-glucose-6-phosphate, d-arabinose-5-phosphate, and d-sedoheptulose-7-phosphate were 6.3, 13.2 and 3.0 nmol per min per 5 × 10(8) bacteria, respectively. d-Ribulose-5-phosphate and d-xylulose-5-phosphate did not inhibit transport of the above substrates, whereas d-ribose-5-phosphate was a weak inhibitor of d-sedoheptulose-7-phosphate transport.